Early-Season Corn Response to Broadcast Pre-Plant Phosphorus Fertilizer Application - G. A. Roa-Acosta; D. A. Ruiz Diaz (Kansas Agricultural Experiment Station Research Reports, 2022)
The objective of this study was to evaluate early-season corn response to different rates of preplant broadcast phosphorus fertilizer and determine the optimum levels using four different soil test methods. The study was conducted in 11 locations across Kansas in 2021. The experimental design is a randomized complete block design with four replications. Fertilizer treatment consisted of five rates of phosphorus fertilizer (0, 30, 60, 90, and 120 lb/a of P2O5). Fertilizer was applied one time by broadcast pre-plant. Soil samples were collected at 0- to 6-in. deep before treatment application, composited by blocks, and analyzed for soil test phosphorus using Mehlich 3, Haney H3A, Bray 1, and Bray 2 test methods. Whole plant sampling at V6 was collected for phosphorus uptake analysis. Results show that using early season phosphorus uptake response provided critical levels of 23 and 17 ppm of phosphorus for the Mehlich 3 and Bray 1 methods, respectively. For the Haney H3A method, the critical level was estimated at 15 ppm and for the Bray 2 method had an estimated critical value of 69 ppm. Phosphorus uptake at early season (V6) showed a significant response to broadcast phosphorus fertilization at four of eleven sites.
Keywords: phosphorus; early season; corn; soil test; phosphorus uptake